Factors Related to Pre-Operative Anxiety Among Older Adult Undergoing General Surgery in Jinzhou, China - Zhang, Yaqian; Toonsiri, Chanandchidadussadee (วารสารคณะพยาบาลศาสตร์ มหาวิทยาลัยบูรพา, 2025)
As a special group of general surgical patients, elderly patients have relatively weak mental ability, and the problem of pre-operative anxiety is more prominent. This correlational descriptive study aimed to identify factors related to pre-operative anxiety among older adult undergoing general surgery in Jinzhou, China. A simple random sampling method was used to recruit the sample of 82 older adults undergoing general surgery in the Third Affiliated Hospital of Jinzhou Medical University in Jinzhou, Liaoning Province, China. Research instruments included questionnaires to gather data for demographic information, State Anxiety Inventory (S-AI), and Social Support Rating Scale (SSRS). Descriptive statistics and point biserial correlation coefficients, Pearson’s product moment correlation coefficients were used to analyze the data. The results revealed that most of the sample (87.80 %) had moderate pre-operative anxiety (score 41-60). For correlation analysis, pre-operative anxiety was significant negatively correlated with age and social support (r = -0.268, p < .05; r = -0.508, p < .01), and positively correlated with married marital status (r =0.398, p < .01). The findings suggest that nurses and other health care providers could apply these study results to develop activities/ programs to prevent pre-operative anxiety in older adults undergoing general surgery by focusing on enhancing social support.